Seasonal changes in body size and oil sac volume of three planktonic copepods, Paracalanus parvus (Claus, 1863), Pseudocalanus newmani Frost, 1989 and Oithona similis Claus, 1866, in a temperate embayment: what controls their seasonality? - Arima, D., A. Yamaguchi, Y. Abe, K. Matsuno, R. Saito, H. Asami, H. Shimada & I. Imai (Crustaceana, 2014)
Seasonal changes in body size (prosome length: PL) and oil sac volume (OSV) of the three most numerically abundant copepods in Ishikari Bay, northern Sea of Japan, Paracalanus parvus (Claus, 1863), Pseudocalanus newmani Frost, 1989 and Oithona similis Claus, 1866, were studied using monthly samples collected through vertical hauls of a 100-μm mesh NORPAC net from March, 2001 to May, 2002. Seasonal changes in PL were common for the three species and were more pronounced during a cold spring. PL was negatively correlated with temperature, and this relationship was described well using the Bˇelehrádek equation. Seasonal changes in OSV exhibited a species-speciﬁc pattern, i.e., OSV was greater during a warm summer for P. parvus and was greater during a cold spring for P. newmani and O. similis. The OSV peak period corresponded with the optimal thermal season of each species. The relative OSV to prosome volume of the small copepods (0.6-0.8%) was substantially lower than that of the large copepods (20-32%). These facts suggest that the oil sac of small copepods is not used for overwintering or diapauses or during periods of food scarcity, but is instead used as the primary energy source for reproduction, which occurs during the optimum thermal season of each species.